MALLAMPATI TEST AS A PREDICTOR OF LARYNGOSCOPIC VIEW - Adamus, Milan; Fritscherova, Sarka; Hrabalek, Lumir; Gabrhelik, Tomas; Zapletalova, Jana; Janout, Vladimir (Biomedical papers, 2010)
Aim: To determine the accuracy of the modified Mallampati test for predicting difficult tracheal intubation.Design: A cross-sectional, clinical, observational, non-blinded study. A quality analysis of anesthetic care. Setting. Operating theatres and department of anesthesiology in a university hospital.Material and methods: Following the local ethics committee approval and patients' informed consent to anesthesia, all adult patients (> 18 yrs) presenting for any type of non-emergency surgical procedures under general anesthesia requiring endotracheal intubation were enrolled. Prior to anesthesia, Samsoon and Young's modification of the Mallampati test (modified Mallampati test) was performed. Following induction, the anesthesiologist described the laryngoscopic view using the Cormack-Lehane scale. Classes 3 or 4 of the modified Mallampati test were considered a predictor of difficult intubation. Grades 3 or 4 of the Cormack-Lehane classification of the laryngoscopic view were defined as impaired glottic exposure. The sensitivity, specificity, positive and negative predictive value, relative risk, likelihood ratio and accuracy of the modified Mallampati test were calculated on 2x2 contingency tables.Results: Of the total 1,518 patients enrolled, 48 had difficult intubation (3.2%). We failed to detect as many as 35.4% patients in whom glottis exposure during direct laryngoscopy was inadequate (sensitivity 0.646). Compared to the original article by Mallampati, we found lower specificity (0.824 vs. 0.995), lower positive predictive value (0.107 vs. 0.933), higher negative predictive value (0.986 vs. 0.928), lower likelihood ratio (3.68 vs. 91.0) and accuracy (0.819 vs. 0.929).Conclusion: When used as a single examination, the modified Mallampati test is of limited value in predicting difficult intubation.
Keywords: Mallampati test/Cormack-Lehane grade/Laryngoscopy/Difficult intubation/Prediction